Gendered Impacts of COVID-19 in Developing Countries - Titan Alon; Matthias Doepke; Kristina Manysheva; Michèle Tertilt (Institute of Labor Economics (IZA), 2022)
In many high-income economies, the recession caused by the Covid-19 pandemic has resulted in unprecedented declines in women's employment. We examine how the forces that underlie this observation play out in developing countries, with a specific focus on Nigeria, the most populous country in Africa. A force affecting high- and low-income countries alike are increased childcare needs during school closures; in Nigeria, mothers of school-age children experience the largest declines in employment during the pandemic, just as in high-income countries. A key difference is the role of the sectoral distribution of employment: whereas in high-income economies reduced employment in contact-intensive services had a large impact on women, this sector plays a minor role in low-income countries. Another difference is that women's employment rebounded much more quickly in low-income countries. We conjecture that large income losses without offsetting government transfers drive up labor supply in low-income countries during the recovery.
Keywords: E32; J16; J20; O10; 330; COVID-19; pandemics; women's labor supply; gender equality